Acrylamide-induced alterations in lungs of mice in relation to oxidative stress indicators. Issue 9 (2nd September 2019) - Batoryna, Marta; Semla-Kurzawa, Magdalena; Zyśk, Bartłomiej; Bojarski, Bartosz; Formicki, Grzegorz
Abstract: The aim of the experiment was to study the influence of acrylamide (ACR) on major antioxidants in the lungs of Swiss mice. The experiment was conducted on male mice that were 8 weeks old. The mice were exposed to ACR at a single dose of 26 µg per animal, which was administered orally. Mice were anesthetized 3, 24, and 48 h after the ACR gavage. Next, histopathological and biochemical analyses of GSH concentration and the activities of SOD, GPx, and CAT were performed in the lungs. Animals exposed to ACR showed demonstrated symptoms of inflammation in lungs, hypertrophy of bronchiolar epithelium, and hyperplasia of alveolar epithelium. GSH concentration was significantly decreased 3 h after ACR gavage, which was followed by a significant increase 48 h after ACR gavage. Similarly, SOD and GPx demonstrated decreased activities 3 h after exposure to ACR, followed by increased activities 48 h after exposure to ACR. CAT activity was significantly increased 24 and 48 h after exposure to ACR. We conclude that oral exposure of mice to ACR results in alterations of lung microstructure, accompanied by the symptoms of redox imbalance.